The Palestinian-Israeli Conflict in Tamim Al-Barghouti’s Nafsi Al-Fida’: A Sociological Study of Literature - Naviza, Ummu Kultsum; Zawawi, Moh. (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2025)
The prolonged conflict between Palestine and Israel, particularly in the Gaza Strip, has caused widespread humanitarian suffering and has become a recurring theme in contemporary Arabic literature. One prominent example is Tamim Al-Barghouti's poem Nafsi al-Fida', written in response to Israel's military aggression against Gaza in 2008-2009 (Operation Cast Lead). This study aims to explore how the poem represents the social reality of the Palestinian-Israeli conflict through a sociological approach to literature. Employing a qualitative descriptive method, the research combines textual analysis of the poem with triangulated sources from international media reports and humanitarian organization documents to ensure data validity. Using Alan Swingewood’s theory of literary sociology, the study interprets the poem as a social product that both reflects and critiques the lived experiences of society under conflict. The analysis reveals that Al-Barghouti’s use of vivid imagery, metaphors of resistance, and contrasts between life and death encapsulates the political and humanitarian dimensions of Gaza’s suffering, depicting Hamas’ political victory, armed resistance, underground defense strategies, white phosphorus bombings, and the devastation of civilian life. These aesthetic choices transform the poem into both an artistic and sociological document, bridging emotion with historical testimony. The findings conclude that Nafsi al-Fida’ not only serves as a record of Palestinian suffering but also contributes to shaping Palestinian literary identity and political discourse by asserting poetry as a form of cultural resistance.